Unintended Consequences of Early Exposure to Policing: Assessing Long-Term Effects of Police Stops During Adolescence in England and Wales. - Kyprianides, Arabella; Ali, Amal; Petnga-Wallace, Pele; Quinton, Paul; Oliveira, Thiago R (British Journal of Criminology, 2026)
This study examines the unintended life-course consequences of being stopped by the police in England and Wales before age 14 using data from the UK Millennium Cohort Study (N  = 9,159). We investigate the predictors of early police contact and their associations with outcomes such as self-reported offending behaviour, academic achievement, and mental health over 3 years. Violent offending, knife carrying, non-violent offending, gang membership, alcohol use and cannabis use are linked to higher likelihoods of police contact by age 14. Police stops at this age are associated with increased violent offending, reduced educational aspirations and outward-facing psychological responses, namely greater conduct problems and attentional difficulties, by age 17; and these associations persist after accounting for important variables such as ethnicity. These findings align with labelling, cumulative disadvantage, general strain theories and the stress process paradigm.